Dodine an effective alternative to copper for controlling Venturia oleaginea, the causal agent of pea-cock eye disease, in highly infected olive trees - Almadi, Leen; Frioni, Tommaso; Farinelli, Daniela; Paoletti, Andrea; Cinosi, Nicola; Rosati, Adolfo; Moretti, Chiaraluce; Buonaurio, Roberto; Famiani, Franco (Frontiers in Plant Science, 2024)
A trial was carried out in central Italy in an olive orchard of cultivar Moraiolo, highly infected by Venturia oleaginea. The aim of the investigation was to evaluate the effects of autumn and spring applications of copper oxychloride or dodine to control the disease. Non treated trees were used as the control. The effects of the fungal attacks on leaves and inflorescence development confirmed the high susceptibility of the cultivar Moraiolo to the disease. The results show that in trees heavily infected, but with most of the infected leaves at the early stage of the disease (asymptomatic phase), treatments with dodine had a curative effect, with consequent reduction in the appearance of symptomatic leaves and defoliation with respect to the control or copper-treated trees. The use of dodine against the autumnal attacks of V. oleaginea allowed most of the old leaves to be maintained until the new ones had formed, which is important for the growth processes during the early part of the growing season. Overall, the results indicate that to efficiently control the pathogen using copper compounds, treatments must start soon after the beginning of the attack and be repeated in order to maintain the infection at a low level. Dodine can be efficiently used if there is a great increase in infected leaves. The use of dodine to solve particular situations and not for normal repeated use is regulated by the fact that in some countries, Italy included, protocols for integrated pest management allow only one dodine treatment/year.